The Failure Rate of Internal Fixation Increases With Sagittal Displacement of the Femoral Head: A Retrospective Study - Lei Shi; Chen Chen; Junsong Wang; Yuanhao Wu; Jia Li; Houchen Lyu; Quanyi Guo; Peifu Tang (Health Care Science)
ABSTRACT Background The risk of internal fixation failure remains relatively high in stable femoral neck fracture (FNF) (Garden I or II). Preoperative sagittal displacement of the femoral head has been proposed as a potential influencing factor. This study aimed to evaluate the impact of sagittal displacement on the outcomes of cannulated screw internal fixation (CSIF) in patients with stable FNF (Garden I or II) by reconstructing the axial sagittal oblique plane of the fracture using preoperative computed tomography (CT) imaging. Methods This study included 167 patients with FNF who underwent CSIF. The sagittal tilt angle of the femoral head (STAFH) was evaluated using three‐dimensional CT (3D‐CT). The distribution of preoperative STAFH was analyzed, and its independent association with treatment failure was assessed. Treatment failure was defined as the need for revision surgery within 2 years postoperatively due to avascular necrosis, nonunion, or internal fixation failure. Results Among the 167 patients, 9 (5.4%) exhibited anterior tilt (AT) of the femoral head, 158 (94.60%) presented with posterior tilt (PT). A total of 50 patients (29.9%) demonstrated excessive sagittal displacement (AT ≥ 10° or PT ≥ 20°). In the failure group, 80.0% of patients had excessive sagittal displacement compared to 28.1% in the healed group. Excessive sagittal displacement was significantly associated with an increased risk of surgical failure (odds ratio: 11.953, 95% CI: 3.656–39.083, p < 0.05). Conclusions In patients with Garden I or II FNF, greater preoperative sagittal displacement of the femoral head was correlated with a higher likelihood of CSIF failure. AT ≥ 10° or PT ≥ 20° were identified as independent predictors of CSIF failure in FNF patients. Nevertheless, these findings still require confirmation through prospective, multi‐center clinical trials with large sample sizes.